A Semi-Autonomous Coal Mine Monitoring Security System Based On Wireless Control Using RTOS - Singh Omkar Ramabhilash; Santosh Kumar Singh (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Novel coal mine administration framework to tackle the ongoing observing and profoundly effective safeguard issues of underground work stages. In this paper proposing a robot that has the fitness to identify the covered mine and let the client control it remotely to stay away from others conscious causalities. The robot is outfitted with exceptional wheels controlled by H-Bridge module, enabling it to move in every single conceivable bearing. In this venture we concentrate on the security of people and the robot; the robot is outfitted with unique range sensors that assistance in staying away from the snags in the field by extraordinarily recognizing the position of obstructions. For the manufacture of the venture, a unique model made of lightweight temperature safe metal is utilized on which every one of the articles is conveyed. Gas immediate, mischance help ask for, video gushing and voice declaration are the extra components of this framework. Advance, a remote ZigBee is added to the robot, which gets the constant estimations of flame, temperature. ARM microcontroller charges the robot. The camcorder connection to the gadget will transmit the picture in the Motion-JPEG arrange alongside a speaker who will enable us to send the crisis charge with the assistance of the voice message device. The application firmware keeps running on top of a RTOS to deal with multitasking prerequisites of the framework. This strategy has a down to earth profit if diminishing the quantity of causalities, after the execution of the procedure; the robot can be controlled productively with slightest buffering time.